Efficient Traceable Attribute-Based Signature With Update-Free Revocation For Blockchain. (30th December 2021) - Zhang, Jixin; Chen, Jiageng
Abstract: Attribute-based signature (ABS) allows signers with a set of attributes to sign messages anonymously using a specific signing policy. However, previous schemes suffer from some efficiency issues which are not widely applied on the blockchain. In this paper, we investigate ABS regarding its features and efficiency in the blockchain setting and provide our solution correspondingly. To solve the revocation problem of ABS in a more efficient manner, we introduce the update-free revocation function. Instead of the passive attribute expiration approaches, we take the active method to ensure that no parameter updates are required by users after the execution of the revocation function. In terms of efficiency, we first address the problem that the signer has to provide proof for all attributes in the predicate for privacy, which is one of the efficiency bottlenecks for ABS. By taking advantage of the blockchain architecture, we propose a new solution which can achieve the constant signature size and verification cost, while the signing cost can be greatly reduced. The corresponding security levels are satisfied according to their strict criteria. A generic construction as well as an instantiation are provided which is provably secure in the standard model satisfying the newly defined formal security definitions. Finally, a purer primitive is discussed.